2020
DOI: 10.1177/1948550619879907
|View full text |Cite
|
Sign up to set email alerts
|

Forever Foreign? Asian Australians Assimilating to Australian Culture Are Still Perceived as Less Australian Than White Australians

Abstract: Westerners of Asian descent emphasize their engagement with national culture to assert their national identity. The present research investigates whether this strategy effectively enhances observers’ perceptions of Asian Westerners’ national identity. In Study 1 ( N = 160), Australian participants evaluated an Asian or White target, manipulated to be either hyper-Australian or not. In Study 2 ( N = 440), targets were additionally manipulated to be either Australian-born or not. Across both studies, As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Researchers have strongly suggested that the phenotypic “White ideal” permeates across cultures and is internalized by people of Asian descent across the world (Aquino & Steinkamp, 2016; Bissell & Chung, 2009; David & Nadal, 2013; David & Okazaki, 2006; Hall, 1995; Jung & Lee, 2006; Mok, 1998a, 1998b; Murray & Price, 2011). In addition, those residing in Western nations such as the United States are further socialized to understand that the adoption of White norms and ideals is tantamount to being accepted and bolstering one’s social position (Bonilla-Silva, 2013; Kim, 1999; Thai, Barlow, & Hornsey, 2014; Thai, Szeszeran, Hornsey, & Barlow, 2020; Zhou, 2004; Zhou & Xiong, 2005). Given the pervasive idealization of White phenotypicality that has previously been found to affect the phenotypic self-perceptions of Black Americans (Bond & Cash, 1992), it is important to investigate whether East Asians experience a phenotypic actual–ideal discrepancy such that they idealize “Whiter” features.…”
Section: Evidence For An Actual–ideal Discrepancy In East Asiansmentioning
confidence: 99%
“…Researchers have strongly suggested that the phenotypic “White ideal” permeates across cultures and is internalized by people of Asian descent across the world (Aquino & Steinkamp, 2016; Bissell & Chung, 2009; David & Nadal, 2013; David & Okazaki, 2006; Hall, 1995; Jung & Lee, 2006; Mok, 1998a, 1998b; Murray & Price, 2011). In addition, those residing in Western nations such as the United States are further socialized to understand that the adoption of White norms and ideals is tantamount to being accepted and bolstering one’s social position (Bonilla-Silva, 2013; Kim, 1999; Thai, Barlow, & Hornsey, 2014; Thai, Szeszeran, Hornsey, & Barlow, 2020; Zhou, 2004; Zhou & Xiong, 2005). Given the pervasive idealization of White phenotypicality that has previously been found to affect the phenotypic self-perceptions of Black Americans (Bond & Cash, 1992), it is important to investigate whether East Asians experience a phenotypic actual–ideal discrepancy such that they idealize “Whiter” features.…”
Section: Evidence For An Actual–ideal Discrepancy In East Asiansmentioning
confidence: 99%
“…Australian society has been characterised as transitioning from a legacy of Anglo domination and cultural superiority to gradual acceptance of multiculturalism, not unlike other settler societies with recent substantial immigration (Forrest and Dunn, 2006). Prior research, including public opinion surveys, has identified Asian-Australians as an ‘out-group’ of ‘key others to the Australian national imagination’ who face intolerance (Dunn, et al., 2004: 412) and are perceived as less Australian than white migrants, even if they display assimilation with the national culture (Thai, et al., 2020). As physical appearance may be the strongest indicator of who is perceived as Australian – what Andrzej Gwizdalski (2014) called ‘visual belonging’ (see also Ang, 2001) – Asian intercountry adoptees in Australia are likely to face challenges with developing their ethnic identity and confronting racism in different societal contexts.…”
Section: Introductionmentioning
confidence: 99%
“…In American society, Asian Americans are often made to feel that they are not "Americans" and just a group of "forever foreigners" (Thai, 2020). Although many Asians have already integrated into local society, Asian Americans are often asked how long they have lived in the United States or where is their hometown.…”
Section: Portrayals Of Asian Women In Western Mediamentioning
confidence: 99%